Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada PT. Alfa Goldline Realty Tangerang Selatan - Muhammad Okan Fadillah; Uswatun Chasanah (Kampus Akademik Publiser, 2026)
Abstract. This study aims to analyze the influence of work discipline and work environment on employee performance at PT Alfa Goldline Realty, South Tangerang. Data were collected through direct observation, questionnaires, and interviews, using an associative quantitative approach with a questionnaire comprising 10 statements on work discipline, 10 statements on work environment, and 10 statements on employee performance, distributed to 100 employees. The data were analyzed using the Statistical Product and Service Solution (SPSS) for Macbook Version 23 through validity tests, reliability tests, classical assumption tests, coefficient tests, linear regression analysis, and hypothesis testing. The results produced the regression model Y = 7.870 + 0.202 X₁ + 0.552 X₂, with an R Square value of 0.613, indicating that work discipline and work environment simultaneously contribute 61.3% to employee performance, while the remaining 38.7% is influenced by other factors not examined in this study.